Semantic Technology Second Joint International Conference, JIST 2012, Nara, Japan, December 2-4, 2012, Proceedings - Takeda, Hideaki; Qu, Yuzhong; Mizoguchi, Riichiro; Kitamura, Yoshinobu; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the proceedings of the Second Joint International Semantic Technology Conference, JIST 2012, held in Nara, Japan, in December 2012. The 20 full papers and 13 short papers included in this volume were carefully reviewed and selected from 90 submissions. The regular papers deal with ontology and description logics; RDF and SPARQL; learning and discovery; semantic search; knowledge building; semantic Web application. The in-use track papers cover topics on social semantic Web and semantic search; and the special track papers have linked data in practice and database integration as a topic.
Ontology and Description Logics -- A Resolution Procedure for Description Logics with Nominal Schemas -- Get My Pizza Right: Repairing Missing is-a Relations in ALC Ontologies -- Ontological Modeling of Interoperable Abnormal States -- RDF and SPARQL -- SkyPackage: From Finding Items to Finding a Skyline of Packages on the Semantic Web -- Accessing Relational Data on the Web with SparqlMap -- Protect Your RDF Data! -- Learning and Discovery Active Learning of Domain-Specific Distances for Link Discovery -- Interlinking Linked Data Sources Using a Domain-Independent System -- Instance Coreference Resolution in Multi-ontology Linked Data Resources -- Semantic Search -- The Dynamic Generation of Refining Categories in Ontology-Based Search -- Keyword-Driven Resource Disambiguation over RDF Knowledge Bases -- An Automated Template Selection Framework for Keyword Query over Linked Data -- Knowledge Building -- Leveraging the Crowdsourcing of Lexical Resources for Bootstrapping a Linguistic Data Cloud -- Navigation-Induced Knowledge Engineering by Example -- FacetOntology: Expressive Descriptions of Facets in the Semantic Web -- Semantic Web Application -- An Ontological Framework for Decision Support -- Development of the Method for the Appropriate Selection of the Successor by Applying Metadata to the Standardization Reports and Members -- A Native Approach to Semantics and Inference in Fine-Grained Documents -- A German Natural Language Interface for Semantic Search -- In-Use Track -- Social Semantic Web -- Topica – Profiling Locations through Social Streams -- A Community-Driven Approach to Development of an Ontology-Based Application Management Framework -- When Mommy Blogs Are Semantically Tagged -- Applying Semantic Technologies to Public Sector: A Case Study in Fraud Detection -- Semantic Search -- Location-Based Concept in Activity Log Ontology for Activity Recognition in Smart Home Domain -- Improving the Performance of the DL-Learner SPARQL Component for Semantic Web Applications -- DashSearch LD: Exploratory Search for Linked Data -- Entity-Based Semantic Search on Conversational Transcripts Semantic: Search on Hansard -- Special Track -- Linked Data in Practice -- Development of Linked Open Data for Bioresources -- Towards a Data Hub for Biodiversity with LOD -- Linking Open Data Resources for Semantic Enhancement of User–Generated Content -- Korean Linked Data on the Web: Text to RDF -- Database Integration -- Issues for Linking Geographical Open Data of GeoNames and Wikipedia -- Interlinking Korean Resources on the Web.
Keywords: Information storage and retrieval; Artificial intelligence; Database management; Data mining; Information Storage and Retrieval; Artificial Intelligence; Database Management; Data Mining and Knowledge Discovery